Estimasi Dosis Serap dengan Metode Size Specific Dose Estimation (SSDE) dan Risiko Radiasi pada Pemeriksaan CT-Scan Kepala di Rumah Sakit Daerah Mangusada Kabupaten Badung - Saputra, Eka; Sutapa, Gusti Ngurah; Paranditayana, I Nyoman (Universitas Hamzanwadi, 2023)
CT scan -Scan Those originating from X-rays on the head are very risky considering that the tissue in the brain has a greater sensitivity to ionizing radiation when compared to other organs in the human body. Problems will then arise when the use of CT-Scan sourced from X-rays can pose a radiation risk. Based on research conducted by Mathews et al. (2013) reported that at least 680,211 patients who had performed CT-Scan, 3,150 patients were diagnosed with cancer. There is a more accurate method in estimating the dose received by patients, namely using the SSDE. The dose estimation method using SSDE considers geometric factors (body size). The purpose of this study was to see how weight, gender, and age affect SSDE, using 80 patients classified into 4 age groups (children, adults, elderly, and seniors). The results showed that the average effective dose for children was 4.065 mSv for males and 3.706 mSv for females with a significant effect of weight, sex, and age on SSDE because theFCount as big4,640 FTableof 2.215